Analisis Efektivitas Dan Efisiensi Anggaran Pendapatan Dan Belanja Daerah Pada Kantor Dinas Pariwisata Dan Kebudayaan Kabupaten Sikka - Maria Paskalia Dua Vina; Henrikus Herdi; Pipiet Niken Aurelia (Student Scientific Creativity Journal, 2023)
This study aims to determine the effectiveness and efficiency of the Regional Revenue and Expenditure Budget at the Tourism and Culture Office of Sikka Regency in the 2019 – 2021 budget period. expenditure and income in each existing organization. The method used in this research is descriptive qualitative analysis. Data collection techniques in the form of Observation, Interview, and Documentation. The research results for the level of effectiveness of budget implementation in 2019-2021 are overall quite effective and the level of efficiency in 2019-2021 is overall inefficient, while the growth rate has also experienced increases and decreases. The Sikka Regency Tourism and Culture Office should pay attention to the situation and conditions, so that the budget that has been prepared can be realized properly.